2011
DOI: 10.1007/s10327-011-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial wilt of sweet potato caused by Ralstonia solanacearum in Taiwan

Abstract: During the last decade, a new bacterial disease has impaired the yield of vegetable sweet potato (30-80%) in Taiwan. Infected plants developed stunting, root and stem rot, vascular discoloration and wilting. Ten bacterial isolates that caused the same symptoms in sweet potatoes after inoculation were reisolated and classified as Ralstonia solanacearum phylotype I biovar 4 based on physical and molecular analyses. Moreover, these isolates also caused wilting in convolvulaceous, solanaceaous and cruciferous plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
(8 reference statements)
1
6
0
Order By: Relevance
“…In comparison to various hexoses, BS168 exhibited a consistent trend of a higher chemotactic response toward glucose (Figure 1a). This trend aligns with the significant glucose chemotaxis observed in the wild‐type (WT) BS strain MCLB2 (Yen, 2023). The mild chemotactic tendency observed in our study may be attributed to the relatively weaker biofilm‐forming ability of the specific BS strain utilized (McLoon et al, 2011).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In comparison to various hexoses, BS168 exhibited a consistent trend of a higher chemotactic response toward glucose (Figure 1a). This trend aligns with the significant glucose chemotaxis observed in the wild‐type (WT) BS strain MCLB2 (Yen, 2023). The mild chemotactic tendency observed in our study may be attributed to the relatively weaker biofilm‐forming ability of the specific BS strain utilized (McLoon et al, 2011).…”
Section: Resultssupporting
confidence: 78%
“…The strain 168 is one of the domesticated lab strain with moderate biofilm formation (Gallegos‐Monterrosa et al, 2016). Ralstonia solanacearum RS7 was isolated from symptomatic tomato plants at Xinshe Dist., Taichung City, Taiwan (Yen, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial wilt disease caused by soil-borne Ralstonia solanacearum is one of the most devastating bacterial diseases in the tropics, subtropics, and some temperate areas with humid and hot summers, with phylotype IIB-1 strains that are acclimatized to even lower temperatures and have caused significant outbreaks in temperate areas in recent years [1,2]. R. solanacearum affects more than 200 plant species, including many solanaceous plants [3,4]. The yield loss of tomato varies up to 91%, and the losses vary from about 10% to 30% in tobacco and from 33% to 90% in potato [5].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria constantly oozed from the cut end of diseased stems when placed in water. R. solanacearum can be transmitted in various ways, such as root contact, irrigation water, machinery, or insects [3,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable sweet potato (VSP), Ipomoea batatas (L.) Lam., a type of sweet potato that generates many tender shoots but does not produce root tubers, is an important green vegetable source during summer or rainy season in East and South Asia (Lai, Lee, & Chen, ). Yields of VSP have been shown to be reduced by 30%–80% due to bacterial wilt (BW) in Taiwan during the past several years (Chen, Lin, & Chung, ). Propagation is by vine cuttings, and a recent study demonstrated that, Ralstonia solanacearum race 1 biovar 4 (R1bv4) can latently infect such cuttings and serve as the major inoculum source for introducing BW into Taiwan VSP fields (Chen, Lin, Tseng, & Chung, ).…”
Section: Introductionmentioning
confidence: 99%